Mengurai Polarisasi Politik di Kalangan Milenial Peran Komunikasi dalam Pemilu - Imaida Noor Hasibuan; Hasan Sazali (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Abstract Political polarization among millennials has become an increasingly prominent challenge in recent years. This generation, which is a significant potential voter in the 2024 Election, is vulnerable to misleading political campaigns, hate speech and false information spread through social media and digital platforms. High levels of polarization can threaten social cohesion and hinder constructive dialogue in the democratic process. This research aims to explore the role of effective political communication and media literacy in unraveling political polarization among millennials in the 2024 elections. By using a mixed method, this research combines quantitative survey methods, qualitative studies with in-depth interviews and focus group discussions, as well as media content analysis to provide a comprehensive picture of this issue. It is hoped that the research results can provide insight into effective political communication strategies, the importance of cross-group dialogue, and the role of media literacy and political education in reducing polarization among millennials. It is hoped that these findings can contribute to efforts to create a healthier and more constructive political environment in the 2024 elections and the democratic process as a whole. Keywords: Political Polarization, Political Communication, Media Literacy, Millennials, 2024 Election